The Effect of Utilizing Audio Murottal Al-Qur'an and Classical Music on Biology Learning to Increase Students' Learning Concentration - Abubakar Sidik Katili; Herinda Mardin; Jusna Ahmad; Ani M. Hasan; Masra Latjompoh; Novi Safitri Lamangida (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to improve students' learning concentration by using audio Murottal Al-Qur'an and Classical Music on Fungi material. The hypothesis studied in this study is that there is an effect of utilizing audio Murottal Al-Qur'an and classical music on increasing the concentration of learning of high school students at 1 Kabila. The research method used is quasi experiment. The research design is Pretest Posttest Control Group Design. The population in the study were all students of class X SMAN 1 Kabila, which were taken using purposive sampling technique. The results showed that there was a significant difference between before and after treatment. Because there is a difference, it is said that there is an effect of utilizing audio Murottal Al-Qur'an and classical music on students' learning concentration with a statistically significant p-value that is lower (p = 0.000) < than the alpha value  = 0.05. This is also reflected in the improvement of students' learning outcomes which shows that both methods are at the level of quite effective, with an N-Gain value of Murottal Al-Qur'an of 64.49% and Classical Music of 60.73%. Thus, it can be concluded that there is an effect of utilizing audio Murottal Al-Qur'an and classical music on increasing the learning concentration of students of SMA Negeri 1 Kabila.